The plastic men [videorecording (DVD)] - Gonzalez, Samuel, Jr; Preston, James; Fichtner, William (Glass House Distribution, 2025)
Vietnam veteran Jonathan Teller, tormented by guilt and haunted by delusions, prepares to end his own life. As he grapples with reality, a chance encounter disrupts his decision, leaving his fate uncertain.